Impact of closely-coupled triple-pilot and conventional double-pilot injection strategies in a LD diesel engine. (15th June 2019) - Denny, Michael; Holst, Fredrik; Helmantel, Arjan; Persson, Håkan; Tunestål, Per; Andersson, Öivind
Highlights: A double-pilot and two triple-pilot diesel injection strategies are compared. The triple-pilot injection strategies significantly reduce the combustion noise. The occurence frequency of the local heat release rate (HRR) peaks matches strong frequencies responsible for combustion noise. A new metric, the Ratio of Reduced Heat Release (RRHR) is developed for HRR analysis. Combustion noise is reduced by reducing the RRHR, making a more linear HRR. Abstract: Three injection strategies are compared in a light-duty (LD) diesel engine at a medium load point. One strategy, representative of a Euro 6 LD injection strategy, has a double-pilot/main/single-post sequence. There is a modest temporal spacing after the first pilot and second pilot. Additional strategies add a third pilot and greatly reduce the spacing after the pilots. These pilots are referred to as being "closely-coupled" to each other and the main injection. For the double-pilot strategy, there is significant undulation of the cylinder pressure around TDC. In contrast, the closely-coupled triple-pilot strategies show notably smaller undulations in their pressure traces. Despite increases in peak pressure rise rate, combustion noise is reduced in both triple-pilot strategies. An analysis of each strategy's heat release rate (HRR) trace shows that the close spacing of the pilot injections drastically reduces the drop in HRR between each subsequent local peak in combustion from each injection. A new metric is developed in order to quantify these drops, called the Ratio of Reduced Heat Release (RRHR). It is found that in order to reduce combustion noise, the RRHR should be minimized. Further analysis into the combustion noise shows that the occurence frequency of the local HRR peaks matches strong frequencies responsible for combustion noise, and furthermore that the reduction in combustion noise is not due to the geometry of the combustion chamber. The modification of the HRR trace by implementing closely-coupled triple-pilot injection strategies allows combustion to be phased earlier, improving efficiency while also reducing combustion noise.